Efficacy and Safety of Tildrakizumab in Older Patients: Pooled Analyses of Two Randomized Phase III Clinical Trials (reSURFACE 1 and reSURFACE 2) Through 244 Weeks - Elke L. M. ter Haar; Juul M. P. A. van den Reek; Kristian Gaarn Du Jardin; Almudena Barbero-Castillo; Elke M. G. J. de Jong; Satish F. K. Lubeek (Acta Dermato-Venereologica, 2023)
The evidence on treating older patients with psoriasis with modern biologics is scarce. This study compared the efficacy and safety of tildrakizumab among younger and older patients with psoriasis (< 65/≥ 65 years) in a post hoc analysis of 2 phase III trials (reSURFACE1/2, n = 1,862). Tildrakizumab 100 mg/200 mg was administered at weeks 0/4/every 12 weeks thereafter. At week 28, patients with ≥ 75% improvement in baseline Psoriasis Area and Severity Index (PASI75) in reSURFACE1 were re-randomized to the same tildrakizumab dose or placebo; in reSURFACE2, PASI75 responders to 200 mg were re-randomized to tildrakizumab 100 mg or 200 mg; PASI75 responders to 100 mg maintained their dose. At weeks 64/52 (reSURFACE1/2), PASI50 responders entered an extension period (weeks 256/244). Outcomes were proportion of patients with PASI < 3, Dermatology Life Quality Index (DLQI) 0/1, comorbidities, comedication, and side-effects. The proportion of patients with a PASI < 3 was similar and maintained (tildrakizumab 100 mg and 200 mg, week 244: 83.3% and 84.1%/92.3% and 100.0%); DLQI 0/1 proportions at week 52 were 66.8% and 72.0%/68.3% and 81.3%. Comorbidity and comedication were more common in older patients. The safety profile of tildrakizumab appeared favourable in both groups. Tildrakizumab in patients ≥ 65 years appears effective and safe in long-term psoriasis management. These findings might assist treatment selection and overcome treatment reluctance.